Medidas de control para prevenir desórdenes musculoesqueléticos en trabajadores administrativos de Global Holding Group (2021)
Global Holding Group is a business group in which part of its staff performs administrative activities, these administrative activities according to a data collection carried out to trigger in its staff discomfort in upper extremities, these discomforts have occurred mostly in people who have been in the organization for more than a year, the results are provided by certain methods of collecting information on health states carried out.